Neurosurgery of epilepsy, movement disorders and pain. Issue 8 (August 2021) - Ellenbogen, Jonathan R.; Ashkan, Keyoumars
Abstract: Functional neurosurgery involves the surgical management of a wide range of neurological diseases with the aim of treating conditions such as movement disorders, spasticity, epilepsy and intractable pain. Functional neurosurgery began with ablative surgical techniques involving destruction of neural structures responsible for the aberrant neural pathways/networks causing pathology. In more recent years there has been a move away from the creation of permanent destructive lesions towards modulation of the neural networks utilizing neuromodulation. Neuromodulation therapies include invasive (e.g. deep brain stimulators, cortical stimulators, vagal nerve stimulators and spinal cord stimulators) and non-invasive (e.g. transcranial magnetic stimulation) approaches that involve the application of electrical stimulation to drive or inhibit neural function within a circuit. Most implantable neuromodulation systems include three primary components: stimulating electrode(s) with contacts at the tip through which electricity is delivered, an implantable pulse generator (IPG) that serves as a signal generator/battery pack, and the extension cable(s) to subcutaneously connect the electrode(s) to the IPG. In this article we primarily focus on the current role of neuromodulation in treating movement disorders, epilepsy and pain, and also consider emerging and evolving applications.